110 Missing: verbal autopsy narratives lack detail for drowning intervention design in Tanzania. (20th November 2022) - Mrema, Sigilbert; Baraka, Jitihada; Sindall, Rebecca; Mecrow, Thomas
Abstract : Background: Mortality data is routinely collected through verbal autopsy (VA), but narratives for injury deaths provide insufficient detail for intervention development. This presentation will summarise findings from a review of drowning VA narratives from four large health and demographic surveillance systems (HDSS) in Tanzania, and present recommendations for improved VA narrative collection. Methods: Data on all drowning deaths for 2008–2014 were extracted from the records of four HDSS sites in Tanzania (representing 1.05 million people), by linking VA and cause of death records. 215 drowning deaths were identified, with 143 records included in the study; 73 records were rejected as they were incomplete. Findings: 30% of drowning deaths were amongst children aged 1–4 years and 70% of deaths were males. The most common location of deaths were rivers, wells, and ponds. The most common activity prior to drowning was playing near water for children, and fishing from a boat or crossing water for adults. However, narratives were very short and provided limited information that could be used to inform intervention design. Conclusion: VA narratives are vital for understanding injury deaths and developing appropriate interventions but guidance on collecting narratives needs strengthening to ensure useful information is captured. Learning Outcomes: Improved guidance is needed for collecting VA narratives for injury deaths, including drowning. It is recommended that this includes prompts to identify location and time of death, weather conditions, attempts to rescue or seek treatment after the injury, and the presence or use of relevant safety equipment.